Eleventh hour security+ : exam SYO-201 study guide - Dubrawsky, Ido.; ScienceDirect eBooks (Rockland, Mass. : Syngress ; Oxford : Elsevier Science [distributor], 2009)
This book will focus on just the essentials needed to pass the Security+ certification exam. It will be filled with critical information in a way that will be easy to remember and use for your quickly approaching exam. It will focus on the main objectives of the exam and include the following pedagogy for ease of use in those final hours.
Front Cover; Eleventh Hour Security+; Copyright Page; Contents; About the Authors; CHAPTER 1 Systems Security; CHAPTER 2 OS Hardening; CHAPTER 3 Application Security; CHAPTER 4 Virtualization Technologies; CHAPTER 5 Network Security; CHAPTER 6 Wireless Networks; CHAPTER 7 Network Access; CHAPTER 8 Network Authentication; CHAPTER 9 Risk Assessment and Risk Mitigation; CHAPTER 10 General Cryptographic Concepts; CHAPTER 11 Public Key Infrastructure; CHAPTER 12 Redundancy Planning; CHAPTER 13 Controls and Procedures; CHAPTER 14 Legislation and Organizational Policies; Index.
Print version record.
Elsevier
Safari Books Online
Keywords: Computer security -- Examinations -- Study guides; Computer networks -- Security measures -- Examinations -- Study guides; Electronic data processing personnel -- Certification; Computer networks -- Security measures -- Examinations; Computer security -- Examinations; Electronic data processing personnel -- Certification; Electronic books